IMPROVING THE COMPETENCY OF MOLECULAR GENETICS FOR MGMP BIOLOGY TEACHERS IN SENIOR HIGH SCHOOL IN SURABAYA - Sugiharto, Sugiharto; Hayati, Alfiah; Amin, M. Hilman F. (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Molecular Genetics is a compulsory subject in grade 12 of senior high school, covering discussions on Genetic Substances (DNA and RNA), Heredity, Protein Synthesis, Mutations and Biotechnology. Many seniors high school students have difficulty understanding this course, so their report book scores are below the KKM. One of the problems is no practicum to apply this subject because it is constrained by tools, materials, and the skills of the teaching staff at each school. Teachers are a very strategic intermediate target because they will explain directly to their students. The purpose of this community service activity is to improve the competence of teachers who are members of the MGMP Biology in Surabaya, especially in the molecular field. This activity was carried out on Saturday, June 30, 2024, attended by 24 participants coordinated by the Head of the MGMP Biology Surabaya, located at the Molecular Genetics Laboratory, Department of Biology, Faculty of Science and Technology, Airlangga University. During the training, participants were given courses and practicums such as the use of micropipettes, the DNA isolation process, the PCR method and the DNA electrophoresis process. The results of the training showed an increase in teachers' understanding as seen from the comparison of achievement scores between the pre-test (highest score = 50, range of score ​​10 – 20 = 45.83%) and post-test (highest score = 80, range of score ​​10 – 20 = 29.17%); the enthusiasm of participants during the delivery of the courses, practicums and discussions; and the satisfaction index value (above 95%) given by participants. It can be concluded that the Molecular Genetics technique training activities using the PCR and Electrophoresis methods can improve the competence and skills of MGMP Biology Surabaya teachers as an effort to support the learning process in senior high schools. From these results, it is hoped that teachers can be clearer when explaining Molecular Genetics material to their students so that students can understand the material more easily.